Molecular evaluation of five different isolation methods for extracellular vesicles reveals different clinical applicability and subcellular origin. Issue 9 (22nd July 2021) - Veerman, Rosanne E.; Teeuwen, Loes; Czarnewski, Paulo; Güclüler Akpinar, Gözde; Sandberg, AnnSofi; Cao, Xiaofang; Pernemalm, Maria; Orre, Lukas M.; Gabrielsson, Susanne; Eldh, Maria
Abstract: Extracellular vesicles (EVs) are increasingly tested as therapeutic vehicles and biomarkers, but still EV subtypes are not fully characterised. To isolate EVs with few co‐isolated entities, a combination of methods is needed. However, this is time‐consuming and requires large sample volumes, often not feasible in most clinical studies or in studies where small sample volumes are available. Therefore, we compared EVs rendered by five commonly used methods based on different principles from conditioned cell medium and 250 μl or 3 ml plasma, that is, precipitation (ExoQuick ULTRA), membrane affinity (exoEasy Maxi Kit), size‐exclusion chromatography (qEVoriginal), iodixanol gradient (OptiPrep), and phosphatidylserine affinity (MagCapture). EVs were characterised by electron microscopy, Nanoparticle Tracking Analysis, Bioanalyzer, flow cytometry, and LC‐MS/MS. The different methods yielded samples of different morphology, particle size, and proteomic profile. For the conditioned medium, Izon 35 isolated the highest number of EV proteins followed by exoEasy, which also isolated fewer non‐EV proteins. For the plasma samples, exoEasy isolated a high number of EV proteins and few non‐EV proteins, while Izon 70 isolated the most EV proteins. We conclude that no method is perfect for all studies, rather, different methods are suited depending on sample type and interest in EV subtype, in addition to sample volume and budget.